Water sorption and diffusion properties of spray-dried dairy powders containing intact and hydrolysed whey protein. (May 2016) - Kelly, Grace M.; O'Mahony, James A.; Kelly, Alan L.; O'Callaghan, Donal J.
Abstract: The aim was to compare the effect of intact or hydrolysed whey protein in spray-dried lactose/protein powders on water diffusion properties and microstructure. Dispersions of protein/lactose (0.21:1) containing either intact or hydrolysed whey protein were spray-dried at pilot scale, and physical properties were determined. Lactose/hydrolysed whey protein powders had significantly increased ( P  < 0.05) particle density, resulting in lower bulk density and occluded air, and higher interstitial air. Moisture sorption analysis at 25 °C showed that dispersions containing intact whey protein exhibited lactose crystallisation at a lower relative humidity (RH) compared to the dispersions containing hydrolysed whey protein. Hydrolysed whey protein dispersions had a lower monolayer moisture value (mm ) than intact whey protein dispersions, as calculated using the Guggenheim–Anderson–de Boer (GAB) equation. Water diffusivity, determined at 25 °C from water sorption kinetics and the application of a mathematical model based on Fick's 2nd law, was significantly different ( P  < 0.05) with respect to the presence of intact or hydrolysed whey protein over the RH range examined (0–60% RH), except at 40% RH. The presence of hydrolysed whey protein resulted in a significantly higher ( P  < 0.05) water diffusivity in powders, with potential implications for hygroscopicity, caking, stickiness and flowability in humid environments. Highlights: Higher RH was required to crystallize powders containing hydrolysed whey protein. Higher diffusion of moisture occurred with hydrolysed whey protein. Post-crystallisation structure was more agglomerated with hydrolysed whey protein.